Effects of inspiratory muscle training on respiratory function and repetitive sprint performance in wheelchair basketball players. Issue 9 (4th July 2008) - Goosey-Tolfrey, V; Foden, E; Perret, C; Degens, H
Abstract : Background: There is considerable evidence that respiratory muscle training improves pulmonary function, quality of life and exercise performance in healthy athletic populations. The benefits for wheelchair athletes are less well understood. Therefore, in the present study, influence of inspiratory muscle training (IMT) on respiratory function and repetitive propulsive sprint performance in wheelchair basketball players was examined. Methods: Using a placebo-controlled design, 16 wheelchair athletes were divided to an experimental (IMT; n=8) or placebo (sham-IMT; n=8) group based on selective grouping criteria. 30 dynamic breaths were performed by the IMT group twice daily at a resistance equivalent to 50% maximum inspiratory pressure (MIP), and 60 slow breaths were performed by the sham-IMT group once a day at 15% MIP for a period of 6 weeks. Results: In the IMT group, both MIP and maximum expiratory pressure (17% and 23%, respectively; p≤0.03) were improved. Similar improvements were noted for the sham-IMT group with 23% and 33% from baseline for MIP and maximum expiratory pressure, respectively (p≤0.03). There were no significant changes in pulmonary function at rest and any of the performance parameters associated with the repetitive sprint test (sprint and recovery times, peak heart rate and peak blood lactate concentration). Reported experiences of using the IMT training device suggested "less breathlessness" and "less tightness in the chest during the training". Conclusions: Although there was no improvement in sprint performance, an improved respiratory muscle function and quality of life were reported by participants in both the IMT and sham-IMT groups.